Access to Internet and Internet Shutdown: A Rights Perspective - Dr. Ajay Kumar; Ram Pratap Singh; Shruti Chandra (Journal of Advanced Research in Journalism & Mass Communication, 2021)
Access to the internet is fast becoming a basic right given the plethora of information available on the net these days. In the current scenario, the issue of internet shutdown has become an important concern in India. Internet shutdown affects people socially, psychologically and economically. On one hand, many democratic countries of the world are discussing about digital freedom and human rights, while on the other hand, some countries including India are continuously practicing Internet shutdowns in different parts of their countries. India has become the top country of the world in terms of the numbers of Internet shutdowns. The Internet has become such a prominent source of information for all of us that when Internet connectivity is suspended, many people are affected as they depend on the Internet services for various purposes. Internet shutdown is not only harmful to democracy and governance but also to the economy of the country. Internet shutdowns are direct violations of digital freedom and human rights. The main objective of this paper is to argue that access to internet is a basic right and highlight the problem of Internet shutdown in India and its adverse impact on the lives of Indians. In addition, this paper attempts to highlight a brief history of Internet shutdowns in India. The paper shows how frequent clampdowns on internet affects the economy, as has been the case of Union Territory of Jammu & Kashmir thereby highlighting the case for internet freedom for the survival of the economy especially in Digital India. How to cite this article: Kumar A, Singh RP, Chandra S. Access to Internet and Internet Shutdown: A Rights Perspective. J Adv Res Jrnl Mass Comm 2021; 8(1): 7-14. DOI: https://doi.org/10.24321/2395.3810.202101